Aerosol‐Jet Printed Fine‐Featured Triboelectric Sensors for Motion Sensing. Issue 1 (23rd October 2018) - Jing, Qingshen; Choi, Yeon Sik; Smith, Michael; Ćatić, Nordin; Ou, Canlin; Kar‐Narayan, Sohini
Abstract: Triboelectric motion sensors, based on the generation of a voltage across two dissimilar materials sliding across each other as a result of the triboelectric effect, have generated interest due to the relative simplicity of the typical grated device structures and materials required. However, these sensors are often limited by poor spatial and/or temporal resolution of motion due to limitations in achieving the required device feature sizes through conventional lithography or printing techniques. Furthermore, the reliance on metallic components that are relatively straightforward to pattern into fine features limits the possibility to develop transparent sensors. Polymers would allow for transparent devices, but these materials are significantly more difficult to pattern into fine features when compared to metals. Here, an aerosol‐jet printing (AJP) technique is used to develop triboelectric sensors using a wide variety of materials, including polymers, which can be directly printed into finely featured grated structures for enhanced sensitivity to displacement and speed of motion. A detailed investigation is presented highlighting the role of material selection and feature size in determining the overall resolution of the resulting motion sensor. A three‐channel rotary sensor is also presented, demonstrating the versatility of the AJP technique in developing more complex triboelectric motion sensors. Abstract : Aerosol‐jet printing is used to develop triboelectric motion sensors, based on the generation of a voltage across two dissimilar materials sliding across each other as a result of the triboelectric effect. A wide variety of materials, including polymers, can be directly printed into fine‐featured grated structures for enhanced sensitivity to displacement and speed of motion.